Pengaruh project-based learning berbantuan instagram terhadap literasi lingkungan dan hasil belajar kognitif - Sintya Yuliandini; Hadi Suwono; Sueb Sueb (Universitas Negeri Malang, 2021)
The objectives of the research are: 1) to know the difference of students environment literacy which get Project-Based Leaming (PjBL) assisted instagram and Project-Based Learning (PJBL), 2) to know the difference of cognitive Ic result of students who get Project-Based Learning (PjBL) assisted instagram and Project-Based Learning (PBL). This research uses mixed methods with embedded design, Data were collected guantitatively through pretest and postest, then analyzed by normality test, homogeneity test, hypothesis anakova test, and eflect size calculation. In addition, data. Were collected gualittively through discussions in instagram, guestionnaires, and interviews which were further analyzed by Miles and Huberman model. The results of the research are: 1) there are differences in environmental lteracy of students who received PJBL assisted instagram and PjBL with covariate (pretest) has no effect on environmental and student literacy, and 2) there are difference of cognitive Icarning outcomes of students who received PJBL assisted instagram and PJBL with covariate (pretest) Has no effect on students cognitive Icarning outcomes. Tujuan penelitan yaitu: 1) mengetahui perbedaan literasi lingkungan siswa yang mendapatkan Project-Based Learning (PIBL) berbantuan instagram dan Project-Based Learning (PJBL), 2) mengetahui perbedaan hasil belajar kognitif siswa yang mendapatkan Project-Based Learning (PBL) berbantuan instagram dan Project-Based Learning (PiBL). Penelitian ini menggunakan mixed methods dengan embedded design. Data dikumpulkan secara kuantitafif melalui pretes dan postes, kemudian dianalisis dengan uji normalitas, uji homogenitas, uji hipotesis anakova, dan penghitungan efect size. Selain itu, data dikumpulkan secara kualitatif melalui diskusi di instagram, angket, dan wawancara yang selanjutnya dianalisis dengan model Miles and Huberman. Hasil penelitian yaitu: 1) ada lingkungan siswa yang mendapatkan PjBL berbantuan instagram dan PIBL dengan kovariat (pretes) tidak berpengaruh terhadap literasi lingkungan dan siswa, an 2) ada perbedaan hasil belajar kognitif siswa yang mendapatkan PJBL berbantuan instagram dan PjBL dengan kovariat (pretes) tidak berpengaruh hasil belajar kognitif siswa